The Immune Response to Respiratory Viruses: From Start to Memory - Reijnders, Tom D.Y.; Schuurman, Alex R.; van der Poll, Tom (Seminars in Respiratory and Critical Care Medicine, 2021)
Biomedical research has long strived to improve our understanding of the immune response to respiratory viral infections, an effort that has become all the more important as we live through the consequences of a pandemic. The disease course of these infections is shaped in large part by the actions of various cells of the innate and adaptive immune systems. While these cells are crucial in clearing viral pathogens and establishing long-term immunity, their effector mechanisms may also escalate into excessive, tissue-destructive inflammation detrimental to the host. In this review, we describe the breadth of the immune response to infection with respiratory viruses such as influenza and respiratory syncytial virus. Throughout, we focus on the host rather than the pathogen and try to describe shared patterns in the host response to different viruses. We start with the local cells of the airways, onto the recruitment and activation of innate and adaptive immune cells, followed by the establishment of local and systemic memory cells key in protection against reinfection. We end by exploring how respiratory viral infections can predispose to bacterial superinfection.
Keywords: immune response; respiratory viruses; viral infection